Fear of COVID-19, Stress, and Anxiety in University Undergraduate Students: A Predictive Model for Depression - Rodríguez-Hidalgo, Antonio J.; Pantaleón, Yisela; Dios, Irene; Falla, Daniel (Frontiers in Psychology, 2020)
Depression is a disabling illness which increases the risk of suicide. The COVID-19 pandemic has led to a rise in fear, anxiety, stress and depression among the population: of these, university undergraduates from countries severely affected by COVID-19 are some of the most vulnerable of all, as they face strict lockdown measures and have fewer resources to cope with it. The aim of this study was to analyze the levels of fear of COVID-19, stress, anxiety and depression during lockdown among undergraduates from Ecuador and to test these possible predictors of depression using a model taken from our study of the scientific literature. A total of 640 undergraduates (72% women) between 18 and 47 years old (M = 21.69; S.D = 4.093) were surveyed. The resulting mean levels found for stress, anxiety and depression were above levels considered non-pathological. Women showed higher levels of fear of COVID-19 than men. The statistical prediction for depression showed a good fit. This depression could be related: both directly and positively by fear of COVID-19 and stress, and indirectly, as a result of these two factors, positively mediated by anxiety. Our study concludes by highlighting the important role that the complex relationships between fear, stress and anxiety can play in the development of depression symptoms and how they can be taken into account in programs aimed at preventing and alleviating this disorder. We propose some general measures for reducing fear of COVID-19 and stress, and suggest that specific programs be designed to control and overcome anxiety among undergraduates.